Studying Sustainable Concrete Block Efficiency Production: A Review (Journal of Engineering, 2023)
Worldwide, enormous amounts of waste cause major environmental issues, including scrap tires and plastic, and large waste, a consequence of the demolition of buildings, including crushed concrete, crushed clay bricks, and crushed thermo-stone. From that point, it’s possible to consider that the recycling processes for these materials and using them in the manufacturing field will reduce the adverse effects on the environment of these wastes and the consumption of natural resources. Sustainable concrete blocks can be considered as one of the products produced by using these materials as partial volume replacement of the coarse, fine aggregate, or cement content, considering their dry density, workability, absorption, compressive strength, and thermal conductivity tests evaluate their performance- and conformity with specifications. The results of tests on samples of sustainable concrete blocks showed the feasibility of using demolished building waste as aggregates instead of natural materials for their production.